Urinary Catheter Causing Paracentesis-induced Circulatory Dysfunction - José Guilherme Assis; Joana Rua (Clinical Practice and Cases in Emergency Medicine)
Case Presentation: A 78-year-old male was admitted to the hospital due to acute-on-chronic liver failure with spontaneous bacterial peritonitis. About six liters of a yellow, turbid fluid were collected via indwelling urinary catheter (UC) overnight. He subsequently developed neurological and cardiac dysfunctions. Imaging confirmed bladder perforation and intraperitoneal placement of the UC, establishing the diagnosis of paracentesis-induced circulatory dysfunction due to unintended ascitic fluid drainage. He was stabilized with albumin replacement. The UC was removed, and the bladder injury resolved spontaneously. Discussion: This case depicts a rare complication of urinary catheterization, which underscores the need for careful monitoring and prompt intervention to effectively manage unexpected catheter-related issues.